A novel pilot bioreactor for scaling up biomass and bioactive compounds on Gynura procumbens adventitious root culture - Dannis Yuda Kusuma; Alfinda Novi Kristanti; Yosephine Sri Wulan Manuhara (Indonesian Journal of Biotechnology, 2023)
Bioreactors for adventitious root culture have been developed to obtain biomass and plant bioactive compounds in large quantities. These technologies provide a great opportunity to produce biomass and bioactive compounds more quickly from Gynura procumbens compared to conventional plant cultivation systems. In previous studies, biomass and bioactive compounds of G. procumbens adventitious roots were successfully increased using a small‐scale bioreactor. In this study, a pilot bioreactor the capacity of 19 L polycarbonate gallon was successfully developed. This bioreactor can be sterilized under the pressure of 0.18 MPa for approximately 60 min. While the bioreactor could not be sterilized when the pressure was less than 0.18 MPa damage may have occurred to the bioreactor vessel at pressures exceeding 0.18 MPa. The results of the chemical grade test as root culture media showed that MS‐Tek provided an optimal root biomass compared to MS‐PA after a 35‐day of the culture period. In addition, the productivity of the total phenolics and flavonoids of adventitious root in MS‐PA was higher than in MS‐Tek. This novel pilot bioreactor is suitable for G. procumbens adventitious root culture, and the technical‐grade chemicals are suitable for improving root biomass production.